New theoretical advances in the understanding of autistic “special abilities” - Laurent Mottron, Jade Desrosiers, David Gagnon, Alexia Ostrolenk, WANG Yu, ZHANG Yingying, ZOU Xiaobing (Xin yixue)
The “Enhanced perceptual functioning model” and the “Veridical mapping model” have been proposed to explain the presence and nature of special abilities in autism. Here， we propose an important update to these two models， by combining them with autistic idiosyncratic language development. The “special abilities” of individuals with autism are achieved by redirecting language analyzers toward structured， yet socially unbiased material， which explains how these special skills extend language processing to materials beyond language. Calendar calculation serves as a test of this theory， in which language analyzers are redirected to calendars， a possible consequence of non-social learning. Non-social learning itself results from the bifurcation caused by the absence of social bias in overall information processing. The longitudinal and operational properties of calendar calculation are analogous to the language learning and processing characteristics of neurotypical populations. Combining the “hijacking” of human language analyzer and directing it towards non-communicative， language-like material provides a concise explanation for the common features of most autistic special abilities and integrates and enriches the “Veridical mapping model”.